Multi-Time Scale Economic Optimization Dispatch of the Park Integrated Energy System - Li, Peng; Zhang, Fan; Ma, Xiyuan; Yao, Senjing; Zhong, Zhuolin; Yang, Ping; Zhao, Zhuoli; Lai, Chun Sing; Lai, Loi Lei (Frontiers in Energy Research, 2021)
The park integrated energy system (PIES) plays an important role in realizing sustainable energy development and carbon neutral. Furthermore, its optimization dispatch can improve the energy utilization efficiency and reduce energy systems operation cost. However, the randomness and volatility of renewable energy and the instability of load all bring challenges to its optimal operation. An optimal dispatch framework of PIES is proposed, which constructs the operation models under three different time scales, including day-ahead, intra-day and real-time. Demand response is also divided into three levels considering its response characteristics and cost composition under different time scales. The example analysis shows that the multi-time scale optimization dispatch model can not only meet the supply and demand balance of PIES, diminish the fluctuation of renewable energy and flatten load curves, but also reduce the operation cost and improve the reliability of energy systems.